Endoscopic endonasal approach for pituitary neuroendocrine tumor with septal mucosa incision tailored to tumor extension intending unilateral septal mucosa preservation - Hiroyoshi Kino; Hiroyoshi Akutsu; Shuho Tanaka; Takuma Hara; Yusuke Morinaga; Hidetaka Miyamoto; Rieko Ii; Koutarou Osawa; Eiichi Ishikawa (Scientific Reports)
Abstract Currently, the direct endonasal approach is widely used in endoscopic endonasal surgery (EES) for pituitary neuroendocrine tumor. However, a large posterior septal perforation is inevitable. We routinely utilize a modified para/transseptal approach using the combination of a Killian and a contralateral rescue flap incision (PTSA with K-R incision). Especially, rescue flap incision is used on ipsilateral side of the tumor extension to facilitate lateral expansion of the anterior sphenoidotomy and tumor resection. One hundred eighty-nine patients underwent EES using PTSA with K-R incision in Tsukuba university hospital. Gross total resection (GTR) was achieved in 146 (77.2%) patients. Even in cases of significant lateral tumor extension (Knosp 3 or 4), GTR was achieved in 56 of 90 (62.2%) patients. Among the 168 patients with available rhinological follow-up data, postoperative anterior and posterior septal perforation occurred in six (3.6%) and 18 (10.7%) patients, respectively. Surgical intervention was required in one (0.6%) patient with anterior septal perforation. Thus, PTSA with K-R incision was effective in preserving the nasal septal mucosa on one side and gaining a sufficient surgical corridor with lateral expansion of the anterior sphenoidotomy on the other side. Our strategy may be preferable to improve maneuverability of instruments during tumor resection.